2010
DOI: 10.1586/era.10.73
|View full text |Cite
|
Sign up to set email alerts
|

The origins of urothelial carcinoma

Abstract: It is now widely believed that there are two major pathways for urothelial carcinogenesis. One pathway usually involves mutation of FGF receptor 3 and gives rise to low-grade papillary tumors that frequently recur but seldom invade. By contrast, high-grade urothelial malignancies, including high-grade papillary urothelial carcinoma and urothelial carcinoma in situ (CIS) usually exhibit deletions or mutations of TP53. Urothelial CIS is the most likely precursor of high-grade invasive bladder cancer. It is a 'fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 157 publications
2
35
0
Order By: Relevance
“…The oligoclonal theory holds that a carcinogen causes independent transformation of cells in different locations within the same tissue, resulting in genetically unrelated tumors. These two theories are not mutually exclusive, and it is possible that both phenomena can occur in the same patient (14). The study by Hafner et al (1) seems to support the monoclonal model of synchronous multifocal tumor origin, although the few cases in which clonality was not identified could represent distinct clones.…”
Section: Commentarymentioning
confidence: 98%
See 1 more Smart Citation
“…The oligoclonal theory holds that a carcinogen causes independent transformation of cells in different locations within the same tissue, resulting in genetically unrelated tumors. These two theories are not mutually exclusive, and it is possible that both phenomena can occur in the same patient (14). The study by Hafner et al (1) seems to support the monoclonal model of synchronous multifocal tumor origin, although the few cases in which clonality was not identified could represent distinct clones.…”
Section: Commentarymentioning
confidence: 98%
“…These tumors frequently harbor the same FGFR3 mutations, tend to be genomically stable, and arise in a mulifocal manner (14). Two theories have been proposed to explain multifocality of urothelial cancers.…”
Section: Commentarymentioning
confidence: 99%
“…FGFR3 is an attractive therapeutic target in these cancers because 60% of mutations occur at a single hotspot that is amenable to screening. Both tyrosine kinase inhibition with the FGFR TKI dovitinib and shRNA knockdown of S249C (the most common FGFR3 mutation) have shown preclinical inhibition of cell proliferation in low-grade cancers (11,12). In contrast, high-grade tumors (commonly flat tumors, CIS, or occasionally papillary tumors) have increased invasive potential and show inactivation of the tumor suppressor genes retinoblastoma (RB) and p53.…”
Section: Nonmuscle-invasive Diseasementioning
confidence: 99%
“…ddMVAC had comparable toxicity and a shorter delay to definitive surgery. A metaanalysis of 2,688 individual patients treated in 10 randomized neoadjuvant chemotherapy trials showed no benefit from single-agent cisplatin, but combination cisplatin regimens showed a significant OS benefit (HR ¼ 0.87; 95% CI, 0.78-0.98; P ¼ 0.016), a 13% decrease in risk of death, and a 5% absolute OS benefit at 5 years (45%-50%) versus surgery alone (12). A smaller meta-analysis of 2 Nordic trials also showed an OS benefit, which was greater in T3 compared with T2 disease.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
“…The second theory, the field-effect theory, explains tumor multifocality as a development secondary to the field cancerization effect. In the last scenario, carcinogens cause independent transforming genetic alterations at different sites in the urothelial lining leading to multiple genetically defective tumors (Cheng et al, 2010). That may highlight the existence of different histopathologies in the same specimen.…”
Section: Bladder Cancer Formationmentioning
confidence: 99%